Efficacy of Different Doses of Intra‐Articular Tranexamic Acid for Reducing Blood Loss and Lower Limb Swelling After Total Knee Arthroplasty: A Prospective, Randomized, Controlled Trial - Shuwei Ye; Yue Luo; Qianhao Li; Lijun Cai; Pengde Kang (Orthopaedic Surgery)
ABSTRACT Objective Both blood loss and lower extremity swelling after total knee arthroplasty (TKA) can affect a patient's postoperative recovery. The aim of this trial was to investigate whether different doses of intra‐articular tranexamic acid (TXA) can reduce blood loss and postoperative lower limb swelling. Methods In a prospective, randomized‐controlled trial, a total of 225 patients were randomly assigned to three groups from September 2020 through January 2021: intra‐articular injections of 3 g, 1 g of TXA, or placebo (saline solution). The primary outcome indicators were perioperative blood loss and decreased hemoglobin levels. The secondary outcome indicators were lower extremity swelling, functional recovery indicators (hospital for special surgery [HSS] scores, range of motion), visual analog scale [VAS] scores, and transfusion rates and safety outcomes, including thromboembolic events, incidence of wound‐related complications, and length of hospital stay. One‐way analysis of variance (ANOVA), post hoc Bonferroni correction, Pearson chi‐square test and Fisher exact test were used for statistical analysis. Results Postoperative blood loss was lower in the 1 and 3 g TXA groups (754.00 ± 409.67 mL and 568.70 ± 408.27 mL, respectively) than in the placebo group (977.32 ± 418.69 mL) (p < 0.001). The maximum postoperative decrease in hemoglobin was lower in the 1 and 3 g TXA groups (2.4 ± 0.9 and 1.8 ± 0.9 g/dL, respectively) than in the placebo group (3.1 ± 1.2 g/dL) (p < 0.001). On postoperative Days 1, 2, and 3, the TXA group presented significantly reduced thigh, suprapatellar, and calf swelling and significantly reduced pain scores during exercise. Compared with that in the low‐dose group, perioperative blood loss was further reduced in the high‐dose TXA group (p = 0.006). However, while patients in the TXA group had improved pain scores, Hospital for Special Surgery scores, and joint range of motion at postoperative rest, these differences were not statistically significant. There were no significant differences in thromboembolic events or complication rates among the three groups. Conclusion Topical TXA in total knee arthroplasty was effective in reducing postoperative blood loss by 24%–43% and in reducing postoperative lower extremity swelling and pain during exercise. Higher doses (3 g) of TXA further controlled perioperative blood loss without affecting postoperative lower extremity swelling, and there was no increase in the incidence of related complications during follow‐up. Trial Registration: This study was a single‐center, prospective, randomized controlled trial (RCT). The trial was approved by the Clinical Trials and Biomedical Ethics Committee at our institution (number: 2018.676), all participants provided written informed consent, and the trial was prospectively registered in the Chinese Clinical Trial Registry (ChiCTR2000035271)